2013
DOI: 10.1111/1755-0998.12065
|View full text |Cite
|
Sign up to set email alerts
|

ITS1 versus ITS2 as DNA metabarcodes for fungi

Abstract: The nuclear ribosomal Internal Transcribed Spacer ITS region is widely used as a DNA metabarcoding marker to characterize the diversity and composition of fungal communities. In amplicon pyrosequencing studies of fungal diversity, one of the spacers ITS1 or ITS2 of the ITS region is normally used. In this methodological study we evaluate the usability of ITS1 vs. ITS2 as a DNA metabarcoding marker for fungi. We analyse three data sets: two comprising ITS1 and ITS2 sequences of known taxonomic affiliations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(235 citation statements)
references
References 45 publications
9
217
1
8
Order By: Relevance
“…Although all barcode-primer pair combinations revealed that floristic variables account for the strongest effects in fungal community composition, there were statistically significant primer biases that were not reported in previous studies (Arfi et al 2012;Daghino et al 2012;Blaalid et al 2013). At the level of OTUs, the choice of primer pairs for the ITS1 barcode explained 2% of the community composition, which is less than any environmental predictor group.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Although all barcode-primer pair combinations revealed that floristic variables account for the strongest effects in fungal community composition, there were statistically significant primer biases that were not reported in previous studies (Arfi et al 2012;Daghino et al 2012;Blaalid et al 2013). At the level of OTUs, the choice of primer pairs for the ITS1 barcode explained 2% of the community composition, which is less than any environmental predictor group.…”
Section: Discussioncontrasting
confidence: 58%
“…In strong disagreement with Waud et al (2014), however, the ITS2 amplicon is unsuitable for studies of orchid mycorrhizal fungi due to multiple mismatches to Tulasnellaceae in primers located in the 5.8S rDNA. With technological advances in read length and quality, we advocate the use of full ITS region due to a better choice of forward primers and the presence of critical differences in either ITS1 or ITS2 in many pairs of closely related species (Blaalid et al 2013;Kõljalg et al 2013). Our in silico and in vivo results indicate that combining amplicons of ITS1Fngs and ITS1ngs forward primers effectively accounts for biases arising from primer mismatches and the occurrence of introns (Oja et al 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Selection of candidate gene regions, as well as associated versatile primers, represents the first most crucial step (e.g. Blaalid et al 2013;Zhan et al 2014a). Versatile primers in the paper refer to PCR primers that can be used to successfully amplify all species members in communities of interest.…”
Section: Selection Of Versatile Primers Based On High Resolution Markersmentioning
confidence: 99%
“…Leray et al 2013;Gibson et al 2014). More successful examples have been reported for the rDNA region, including the internal transcribed spacer (ITS), SSU rDNA, and large subunit ribosomal DNA (LSU rDNA), for diverse communities such as microbes (Nossa et al 2010), fungi (Ihrmark et al 2012;Blaalid et al 2013) and plankton (Zhan et al 2014a).…”
Section: Selection Of Versatile Primers Based On High Resolution Markersmentioning
confidence: 99%